2003
DOI: 10.1007/s00426-003-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic movement is attracted more strongly to auditory than to visual rhythms

Abstract: People often move in synchrony with auditory rhythms (e.g., music), whereas synchronization of movement with purely visual rhythms is rare. In two experiments, this apparent attraction of movement to auditory rhythms was investigated by requiring participants to tap their index finger in synchrony with an isochronous auditory (tone) or visual (flashing light) target sequence while a distractor sequence was presented in the other modality at one of various phase relationships. The obtained asynchronies and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
193
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(230 citation statements)
references
References 51 publications
27
193
2
2
Order By: Relevance
“…Correlational coefficients for best fits of the latter model are indicated above the bars 1 autocorrelation). Second, consistent with previous findings , we found evidence of higher order error correction (negative Lag 3 autocorrelation) only when auditory information was present, and in a new finding, particularly when it was less salient (complex rhythm, small magnitude condition).The current study contributes to a growing literature demonstrating that the auditory advantage in sensorimotor synchronization, first observed in comparisons between (auditory) metronome ticks and (visual) flashing lights (e.g., Bartlett & Bartlett, 1959;Chen et al, 2002;Dunlap, 1910;Jäncke et al, 2000;Patel et al, 2005;Repp & Penel, 2002, 2004, may be more nuanced than previously thought. For example, recent studies have shown that visual performance for simple rhythms improves to auditory levels when visual information is continuous rather than discrete (Gan et al, 2015;Iversen et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Correlational coefficients for best fits of the latter model are indicated above the bars 1 autocorrelation). Second, consistent with previous findings , we found evidence of higher order error correction (negative Lag 3 autocorrelation) only when auditory information was present, and in a new finding, particularly when it was less salient (complex rhythm, small magnitude condition).The current study contributes to a growing literature demonstrating that the auditory advantage in sensorimotor synchronization, first observed in comparisons between (auditory) metronome ticks and (visual) flashing lights (e.g., Bartlett & Bartlett, 1959;Chen et al, 2002;Dunlap, 1910;Jäncke et al, 2000;Patel et al, 2005;Repp & Penel, 2002, 2004, may be more nuanced than previously thought. For example, recent studies have shown that visual performance for simple rhythms improves to auditory levels when visual information is continuous rather than discrete (Gan et al, 2015;Iversen et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Repp and Penel [3] observed an effect even for ''soft'' sounds (i.e., low in sound pressure level), but did not specify the levels of those sounds. We used the task paradigm of Repp and Penel [3], in which the tap timing relative to the flash timing is measured while the sound timing relative to the flash timing is systematically varied. Tone bursts were used as the stimuli, and the frequency of the tone was 250, 1,000, or 4,000 Hz.…”
Section: Introductionmentioning
confidence: 90%
“…The thin solid lines are fifth order polynomials fitted to the data points after this adjustment. The fitting was made to indicate the general trend [3]. Although there were appreciable interindividual variabilities in reproducibility and in the patterns of sound-delay effect, we can see a general trend that the mean asynchronies varied with the sound delay, particularly for higher sensation levels.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective for the rower is to synchronize the sound of the bell with the next drum hit. The choice of percussive instruments was motivated by the natural ability for humans to follow rhythmical patterns displayed in the auditory modality in synchronization tasks, as pointed out by Repp and Penel [20].…”
Section: Musical Instrumentsmentioning
confidence: 99%